A escrita do sudoeste da Península Ibérica : velhos dados, novas teorias e a sua importância para o estudo das antigas culturas hispânicas - Correia, Virgílio Hipólito (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The paper draws a revision of current knowledge and theories about the epigraphy of the Ist Iron age of SW Iberia, with a special focus on the problems related to the development of a script and and our understading of the epigraphy it produces. Proposals are made concernig the identification of the signs of that script and the integration of the related language in the Ist millenium AC.